2023
DOI: 10.1002/anie.202219299
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Cu Nanoparticles for the Low‐temperature Photo‐driven Water‐gas Shift Reaction

Abstract: The activation of water molecules in thermal catalysis typically requires high temperatures, representing an obstacle to catalyst development for the low‐temperature water‐gas shift reaction (WGSR). Plasmonic photocatalysis allows activation of water at low temperatures through the generation of light‐induced hot electrons. Herein, we report a layered double hydroxide‐derived copper catalyst (LD‐Cu) with outstanding performance for the low‐temperature photo‐driven WGSR. LD‐Cu offered a lower activation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…It was observed that compared to adsorbed on GaN, and Ni 4 /GaN, H 2 O illustrated the most energy-favorable configuration if it was adsorbed on Ni 3 Fe/GaN. It thus facilitated hydrogen evolution from methanol and water, , which is well consistent with the measured activity and isotope experiments. The theoretical calculations above agree well with the operando DRIFT and in situ EPR spectroscopic characterizations.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that compared to adsorbed on GaN, and Ni 4 /GaN, H 2 O illustrated the most energy-favorable configuration if it was adsorbed on Ni 3 Fe/GaN. It thus facilitated hydrogen evolution from methanol and water, , which is well consistent with the measured activity and isotope experiments. The theoretical calculations above agree well with the operando DRIFT and in situ EPR spectroscopic characterizations.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen, which can be produced from a variety of raw materials, is widely considered as a promising energy carrier to replace fossil fuels. 1,2 Currently, photocatalytic water splitting for hydrogen evolution has been widely considered as a feasible method to convert solar energy…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen, which can be produced from a variety of raw materials, is widely considered as a promising energy carrier to replace fossil fuels. 1,2 Currently, photocatalytic water splitting for hydrogen evolution has been widely considered as a feasible method to convert solar energy into chemical energy. 3–10 Despite many efforts made in the past, such as the development of multifunctional photocatalysts, 11–14 the construction of heterojunctions 15–18 and the loading of co-catalysts, 19–21 the efficiency of photocatalytic hydrogen evolution is still very low.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, non-noble metal catalysts are promising candidates due to their abundant resources. Among the non-noble metal catalysts for the WGS reaction, Cu-based catalysts (e.g., commercial Cu/ZnO/Al 2 O 3 ) have attracted extensive attention over the past decades owing to their remarkable ability to activate CO and dissociate H 2 O. , Nevertheless, Cu-based catalysts have their own drawbacks such as a narrow activation temperature range, poor start/stop cycling behavior, and an easy sintering tendency. Therefore, it is highly desirable to develop robust Cu-based catalysts for the WGS reaction.…”
Section: Introductionmentioning
confidence: 99%